PENGASUHAN BERBASIS NILAI: STRATEGI ORANG TUA DALAM MENANAMKAN MORALITAS DAN ETIKA KEPADA ANAK DI ERA DIGITAL - Mufassiroh Asy-Syauqi, Icha; Indah Nur Bella Sari; Erlina; Umi Hijriyah; Bambang Irfani (LPPM IAD Probolinggo, 2024)
The aim of this research is to explore value-based parenting strategies implemented by parents in instilling morality and ethics in children in the digital era. In this context, advancements in information technology have created new challenges in parenting, particularly related to children's engagement with digital content. This study conducted in-depth interviews with ten parents who have elementary school-aged children. The method is a descriptive qualitative approach. Reduction, presentation, and conclusion drawing are the steps used to conduct data analysis. The research results show that parents use various methods to communicate, supervise technology use, and integrate religious and cultural values in parenting. Parents who effectively teach moral values to their children also tend to talk to them about the positive and negative impacts of digital technology. This study suggests that parents need training and guidance to enhance their ability to navigate the dynamics of the digital era. Keywords: value-based parenting; children's morality; children's ethics; digital era; parenting strategies